RURAL EDUCATION AND SOCIAL JUSTICE: CONTEXTUALIZED PEDAGOGIES FOR RURAL COMMUNITIES (REMUNOM, 2026)
Rural education, historically neglected by urban-centric models, demands a reconfiguration based on social justice and pedagogical contextualization. This study, designed as a theoretical essay grounded in an integrative literature review, analyzes how contextualized pedagogies can transform the reality of rural communities. The central objective is to investigate the effectiveness of Decision Engineering in designing educational solutions that respect rural identity while optimizing the learning flow. The methodology followed the six-stage protocol for integrative reviews, with an analysis of evidence collected between 2021 and 2026. The results demonstrate that the integration of data intelligence and decentralized governance architectures allows for mitigating dropout rates and promoting radical inclusion. It is concluded that the competitive advantage of rural schools lies in the ability to transform traditional knowledge into knowledge assets supported by an ethical and technologically robust infrastructure.